PERSEPSI MASYARAKAT TERHADAP PERAN ORGANISASI KARANG TARUNA DALAM KEHIDUPAN SOSIAL DI DESA TANJUNG DAYANG SELATAN OGAN ILIR - Marwiya; Shomedran; Henny Helmi; Erna Retna Safitri (STKIP Subang, 2026)
This study aims to analyze community perceptions of the role of the Karang Taruna organization in Tanjung Dayang Selatan Village. This research uses a quantitative approach with a descriptive method. The population consists of 1,575 community members, with a sample of 94 respondents selected using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using descriptive statistical methods. The results showed that community perception of the role of Karang Taruna is in the very good category with a percentage of 83.81%. This finding is reflected in four main indicators, namely organizational function, activity benefits, program performance, and activity relevance, all of which are categorized as very good. Karang Taruna has been able to strengthen social interaction, increase youth participation, and provide real benefits to the community. However, several aspects still need improvement, particularly in increasing public understanding of organizational functions, aligning activities with community needs, and improving program planning. Therefore, Karang Taruna is expected to enhance program innovation and community-based planning to achieve more optimal and sustainable organizational performance.